2003
DOI: 10.1016/s1570-9639(03)00147-x
|View full text |Cite
|
Sign up to set email alerts
|

The molecular class C acid phosphatase of Chryseobacterium meningosepticum (OlpA) is a broad-spectrum nucleotidase with preferential activity on 5′-nucleotides

Abstract: The olpA gene of Chryseobacterium meningosepticum, encoding a molecular class C phosphatase, was cloned and expressed in Escherichia coli. The gene encodes a 29-kDa polypeptide containing an amino-terminal signal peptide typical of bacterial membrane lipoproteins. Expression in E. coli results in a functional product that mostly partitions in the outer membrane. A secreted soluble OlpA derivative (sOlpA) lacking the N-terminal cysteine residue for lipid anchoring was produced in E. coli and purified by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…To date, a number of enzymes in this class have been identified including enzymes from Pasteurella multocida (6), Bacillus anthracis (9), Streptococcus equisimilis (24), and Francisella tularensis (unpublished data) or purified and characterized en- zymes from H. pylori (35), E. meningosepticum (29), S. aureus (6), Mycoplasma bovis (33), and H. influenzae (8,37,38). Results from this study suggest that the class C acid phosphatase of C. perfringens possesses many attributes common to those previously examined; however, CppA is devoid of a lipid modification signal sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a number of enzymes in this class have been identified including enzymes from Pasteurella multocida (6), Bacillus anthracis (9), Streptococcus equisimilis (24), and Francisella tularensis (unpublished data) or purified and characterized en- zymes from H. pylori (35), E. meningosepticum (29), S. aureus (6), Mycoplasma bovis (33), and H. influenzae (8,37,38). Results from this study suggest that the class C acid phosphatase of C. perfringens possesses many attributes common to those previously examined; however, CppA is devoid of a lipid modification signal sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Class C enzymes purified and/or characterized thus far include those from Bacillus anthracis (9), Haemophilus influenzae (e [P4]) (37,38), Streptococcus equisimilis (LppC) (24), Staphylococcus aureus (SapS) (6), Helicobacter pylori (HppA) (35), and Elizabethkingia meningosepticum (previously termed Chryseobacterium meningosepticum) (OlpA) (29). Conserved attributes of these enzymes include a metal-containing polypeptide component of 25 to 30 kDa and broad substrate specificity.…”
Section: -(V/a/l)-d-(i/l)-d-e-t-(v/m)-l-x-(n/t)-x-x-y Near the N Termmentioning
confidence: 99%
“…Point mutations in either the conserved aspartate residues or the proposed heme binding site have not been analyzed in H. influenzae for an impact on heme acquisition; however, point mutations of D64 and D66 in H. influenzae reportedly impacted utilization of NAD [7]. Other members of the bacterial class C NSAP family that have been partially characterized include HppA of Helicobacter pylori, OlpA of Chyseobacterium meningosepticum, LppC of Streptococcus equisimilis, and SapS of Staphylococcus aureus [19][20][21][22][23]. Of these only LppC was analyzed with respect to heme utilization and is unable to complement the hemA mutant of E. coli [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, biochemical characterization of another bacterial acid phosphatase of the ''DDDD'' superfamily namely OlpA of Chryseobacterium meningosepticum [16], which belongs to molecular class C, revealed that this enzyme also behaves as a broad-spectrum nucleotidase with a behaviour similar to that of AphA. In fact, both enzymes exhibit a preference for mononucleotides and a similar behaviour with different compounds such as pNPP, Glucose-6-P and h-Glycerol-P.…”
Section: Discussionmentioning
confidence: 99%